1993
DOI: 10.1172/jci116269
|View full text |Cite
|
Sign up to set email alerts
|

Complete testicular feminization caused by an amino-terminal truncation of the androgen receptor with downstream initiation.

Abstract: We have characterized the molecular defect causing androgen resistance in two 46

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
34
0

Year Published

1994
1994
2014
2014

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 87 publications
(38 citation statements)
references
References 27 publications
4
34
0
Order By: Relevance
“…Types of amino-terminal domain mutations include premature stop codons (28), frameshifts (29, 30) and a single missense mutation, (31) and expansions of the homopolymeric CAG trinucleotide repeat (32). In the present report, we characterize a novel molecular mechanism for AIS resulting from a G to A substitution in codon 2 adjacent to the translation initiation codon in the amino-terminal domain of the AR in three related individuals with partial AIS.…”
Section: Discussionmentioning
confidence: 81%
“…Types of amino-terminal domain mutations include premature stop codons (28), frameshifts (29, 30) and a single missense mutation, (31) and expansions of the homopolymeric CAG trinucleotide repeat (32). In the present report, we characterize a novel molecular mechanism for AIS resulting from a G to A substitution in codon 2 adjacent to the translation initiation codon in the amino-terminal domain of the AR in three related individuals with partial AIS.…”
Section: Discussionmentioning
confidence: 81%
“…This AR doublet is also found in the human prostate tumor cell line LNCaP and is believed to reflect posttranslational phosphorylation of the 110-kDa AR gene product (11). In a previous study (12), we identified a mutation in the N-terminal region of the AR gene carried by a 46,XY phenotypic female (R776) with the syndrome of complete testicular feminization; this mutation introduces a premature termination codon in place of the normal AR codon for amino acid 60 (Fig. 1B).…”
mentioning
confidence: 66%
“…Initiator codon mutations are uncommon, but typically they are associated with null alleles as no functional protein is produced [44][45][46][47]. However, in a few cases, translation of the mutant allele initiates from a downstream methionine or other amino acid, producing a truncated protein that retains partial or full function [48][49][50]. The in vitro transcription/translation experiments indicated that the wild-type ankyrin cDNA initiates only from the known initiator methionine and that the ankyrin New Haven cDNA does not utilize an alternate translation initiation codon.…”
Section: Discussionmentioning
confidence: 99%